Diversity, Composition, and Abundance Distribution of Birds in Kariangau Industrial Zone, Balikpapan City, East Borneo - Alexander Kurniawan Sariyanto Putera; Yeni Aryati Mulyani; Dyah Perwitasari Farajallah; Stanislav Lhota; Tadeas Toulec (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
The Kariangau Industrial Zone extends industry from Balikpapan city in the Central Balikpapan to the coast in Western Balikpapan, forming a part of Balikpapan Bay. Our study aimed to estimate the diversity, species composition, and the abundance distribution of birds at the industrial zone of Balikpapan City. Our study contained six replicates each of boat transects on four rivers, the Somber, Getah, Paka Dua, and Wain rivers during the months of May and June 2017. We calculated the Margalef diversity and Bray–Curtis similarity indices to estimate diversity and species composition, whereas bird abundance distributions were analyzed using Paleontological Statistics (PAST) version 3.12. The Getah river had the highest diversity index (4.846), followed by the Somber (3.988), Wain (3.510), and Paka Dua (3.050) rivers. The Bray–Curtis index revealed high similarity in species composition between the Wain and Paka Dua. Our rarefaction analysis showed that the Wain and Paka Dua rivers were well sampled and had lower species richness, with low differences between the observed and expected species richness, than the Somber and Getah rivers. Fisher Log Series Model also showed abundance distribution being highest at Getah (11.170), and lowest at the Paka Dua Rivers (5.221). This observation may be due to heightened industrial activities and boat traffic on each river. Our study provides a useful baseline for future research on the bird assemblages on Balikpapan Bay.